Using Storytelling to Develop English Vocabulary on Early Age Children Measured by Mean Length Of Utterance (MLU) - Rizky Vita Losi; Virdyra Tasril; Rika Widya; Maulana Akbar (ITScience (Information Technology and Science), 2022)
For early childhood, listening to stories can be a very useful stimulation for the development of their language skills. The development of English language skills from an early age plays an important role, because through language, children begin to hone their reasoning and skills by learning to express their thoughts and emotions. This study aimed to measure the Mean of Length Utterance (MLU) in early age children stimulated by storytelling aided by digital printing puppets. This research was a qualitative research conducted at Al-Washliyah Kindergarten. The utterances in English which were stimulated by storytelling by utilizing digital printing puppets became the data in this study. The findings showed that children's English skills developed when the teacher told stories using digital printing puppet media in the learning process. Storytelling is beneficial not only for learning the mother tongue but also for learning foreign languages because it aids in the memorization of new words by stimulating attention, providing excitement, and so on. Children absorb new material faster and better, making language development more accessible.